2014
DOI: 10.1007/s10616-014-9710-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of the some selective estrogen receptor modulators: a review

Abstract: The objective of this article is to review genotoxicological profile of the major selective estrogen receptor modulators, including clomiphene, tamoxifen, toremifene, raloxifene. These drugs have been used for infertility treatment and breast cancer prevention in high risk-women. However, some studies reported that especially tamoxifen is a genotoxic agent and is related with endometrial cancer. Our review indicate that clomiphene and tamoxifen were found as genotoxic agent in majority of the tests. However pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Al-Jassabi et al reported the motivation of oxidative DNA damage in Balb/c male mice and some other cellular sections by tamoxifen (Al-Jassabi et al 2011). In bone marrow cells, Rodrigues et al demonstrated the induction of micronuclei, and reduction of polychromatic erythrocytes formation, in female Wistar-Hannover rats (Rodrigues et al 2012;Yilmaz et al 2014). Moreover, bone marrow depression when taking tamoxifen is a well reported symptom (Sloane 2002;Gail and Wilkes 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Jassabi et al reported the motivation of oxidative DNA damage in Balb/c male mice and some other cellular sections by tamoxifen (Al-Jassabi et al 2011). In bone marrow cells, Rodrigues et al demonstrated the induction of micronuclei, and reduction of polychromatic erythrocytes formation, in female Wistar-Hannover rats (Rodrigues et al 2012;Yilmaz et al 2014). Moreover, bone marrow depression when taking tamoxifen is a well reported symptom (Sloane 2002;Gail and Wilkes 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research has confirmed that long-term TAM treatment is genotoxic, and subsequent investigations have identified various genotoxic consequences of TAM in vivo. In female Wistar-Hannover rats, induction of micronuclei and reduction of polychromatic erythrocyte production was shown in bone marrow cells [48,49]. TAM-loaded PLGA was more successful in this respect; as the concentration is increased, they show reduced absorbency, especially when treated with 200 µgmL -1 .as we demonstrated how DNA was prevented from breaking down.…”
Section: Dna Damage Assaymentioning
confidence: 54%
“…The extent to which underlying conditions associated with subfertility may be causal, vs effects of the drug, has also been debated ( 17 , 36 ). Arguing against this, there is compelling evidence of risks for women using clomiphene citrate including elevated incidence of endometrial and ovarian cancer at higher doses or with prolonged use ( 10 , 12 , 71-74 ).…”
Section: Discussionmentioning
confidence: 99%